Effect of Blockholder Ownership on the Related Party Transactions to the Financial Industries - Supatmi, Supatmi; Primadani, Ines Aprilia (International Journal of Social Science and Business, 2021)
This study aimed to find out blockholder ownership effect on tunnelling or propping related party transactions. Sample researchs were 82 financial industries that listed in Indonesian Stock Exchange in 2017-2019 with 246 observations as panel data. Based on panel data regression test, this study found blockholder ownership had positive effects on tunnelling related party transactions that proxied by related party transactions related to accounts receivable and related party transactions related to assets other than account receivables.Â  Meanwhile, blockholder ownership had no effect on propping related party transactions that proxied by related party transactions related to accounts payable and liabilities other than accounts payable. The study also found blockholder ownership effect on tunnelling related party transactions was bigger than propping. These findings were appropriate with the relevant agency theory about blockholder ownership effect on related party transactions which had the potency on the emergence of agency conflict among the shareholders.